Optimization of the process and formulation for the manufacture of canton-type noodles using coconut residue flour (CRF) - Catalan, Maria Luisa Maderal; Galvez, Flor Crisanta F. (1997., 1997)
The formulation for canton-type noodles with coconut residue flour (CRF) which was acceptable to consumers was optimized using response surface methodology. Phase I involved the determination of the effect of the amount of CRF (0,15 and 30% substitution of wheat flour) and water(29,32 and 35%) on the consumer acceptability of the product. In Phase II, the effect of varying the fat content of CRF (23,28 and 32%) and different frying times (1.5, 2.5 and 3.5 minutes) were studied. Twenty-four panelists evaluated the cooked samples for overall appearance, overall flavor, overall texture and overall acceptability. Raw samples were evaluated for overall appearance. All samples were evaluated using 9-point hedonic scales. Samples with rating of 6 or greater were considered acceptable. Results showed that optimum amount of water to be used was 29-30%. A substitution of wheat flour with CRF up to 22.5% yielded products with acceptable appearance, flavor, texture and overall acceptability. Optimum frying time was between 90-150 seconds (1.5-2.5 minutes). The levels of fat content used in this study did not have any effect on the consumer acceptability of the noodles.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Coconut residue flour; Noodles